Serum ferritin level in patients of allergic rhinitis - Souvagini Acharya; Dandapiti Punam Dora; Kamalini Bepari; Sankar Priyadarshan Nayak (Indian Journal of Allergy Asthma and Immunology, 2025)
BACKGROUND: Allergic rhinitis is the most common form of non-infectious rhinitis and is associated with an IgE-mediated immune response to allergens. It has a negative impact on the quality of life of patients. Iron deficiency and anemia are associated with atopic diseases and good iron status prevents allergy. OBJECTIVES: To study level of serum ferritin in patients of allergic rhinitis and compare this with that of normal subjects. METHODOLOGY: This study was conducted in the department of Otorhinolaryngology, VIMSAR, Burla. The participants were subjected to clinical evaluation and haematological investigations including Complete blood count and Serum ferritin level. This was compared with that of matched healthy subjects taken as controls. The severity of allergic rhinitis was measured using ARIA classification. RESULTS: Among the 40 patients in each group, there were 29 female patients (72.5%) and 11 male patients (27.5%) with a mean age of 35.1 years. The incidence of iron deficiency was significantly higher in patients with allergic rhinitis compared with normal subjects. The average serum ferritin level in cases of AR was 12.03 ng/ml whereas the average level in control subjects was 124.2 ng/ml (p-value <0.0001 as determined by t-test). Also, we found statistically significant difference of serum ferritin level between mild and moderate/ severe cases of allergic rhinitis. CONCLUSION: Prevalence of iron deficiency in patients with allergic rhinitis is higher than in patients without atopic disease. Iron deficiency increases markedly with severity of allergic rhinitis. The level of serum ferritin can be used as a marker for determining the severity of allergic rhinitis.